2022
DOI: 10.3390/jfb13040233
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Antimicrobial Performance of Textiles Coated with ZnO and TiO2 Nanoparticles in a Tropical Climate

Abstract: This paper reports the results of the large-scale field testing of composite materials with antibacterial properties in a tropical climate. The composite materials, based on a cotton fabric with a coating of metal oxide nanoparticles (TiO2 and/or ZnO), were produced using high-power ultrasonic treatment. The antibacterial properties of the materials were studied in laboratory tests on solid and liquid nutrient media using bacteria of different taxonomic groups (Escherichia coli, Chromobacterium violaceum, Pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
1
5
0
1
Order By: Relevance
“…5C). Additionally, this study's elemental percent of ZnONPs matches up to other research (Veselova et al 2022).…”
Section: Tem Sem and Edx Analyses Of Znonpssupporting
confidence: 81%
“…5C). Additionally, this study's elemental percent of ZnONPs matches up to other research (Veselova et al 2022).…”
Section: Tem Sem and Edx Analyses Of Znonpssupporting
confidence: 81%
“…Since ZnO and TiO 2 have no impact on human cells, NP-based wound care solutions utilizing these two oxides are relatively new compared to conventional materials and are safe to employ as antibacterial agents. Veselova et al investigated the long-term antibacterial efficacy of textiles coated with ZnO and TiO 2 nanoparticles in a tropical environment [61]. Cotton bandages containing Ag-and ZnO-NPs and mixed Ag/ZnO-NPs show antibacterial activity and high resistance to Acinetobacter baumannii and Pseudomonas aeruginosa [62].…”
Section: Applications Of Antimicrobial Nanomaterialsmentioning
confidence: 99%
“…Another study by Veselova et. al. showed that TiO2/ZnO composites are capable of only reducing up to 20, 50 and 50 % of C. violaceum, E. coli and P. chlororaphis, respectively, in outdoor conditions [26]. The inhibition capacity of TiO2/ZnO composites were demonstrated to be more ineffective in liquid media conditions where the decrease in the number of CFU compared with the reference sample is less than 10% in both C. violaceum and E. coli.…”
Section: Introductionmentioning
confidence: 99%